A Comparative Analysis of the Principles of Islamic Ethical Trade and the Concept of Liberal International Relations - Nur Rizky Putri Mahadi; Sitti Nurtina (Universitas Bina Mandiri Gorontalo, 2026)
The contemporary international trading system is dominated by the liberalism paradigm, which emphasizes free trade, deregulation, and the accumulation of material profit. However, this system is often criticized for fueling economic inequality and neglecting moral considerations. This study aims to conduct a comparative analysis of the principles of ethical trade in Islamic Economics with the concept of international trade from the perspective of Liberal International Relations. Using a descriptive qualitative method with a literature review approach, this study examines the key literature from both paradigms to identify points of convergence and divergence. The findings reveal similarities between the two concepts in terms of promoting cross-border cooperation, market openness, and rejecting extreme protectionism for the sake of the common good. Nevertheless, a fundamental difference lies in their epistemological foundations. Trade under Liberalism is anthropocentric, oriented towards individual freedom and maximum material gain. Conversely, Islamic ethical trade is theocentric in nature, linking economic activity to moral boundaries, social justice, mutual consent, and the prohibition of exploitative practices. This study concludes that the concept of Islamic ethical trade can serve as a moral corrective to the shortcomings of the liberal free-trade system, with a view to realizing a more just global economic order.